Evaluation of NG-Test CARBA 5 version 2, Cepheid Xpert Carba-R, and carbapenem inactivation methods in comparison to whole-genome sequencing for the identification of carbapenemases in non-fermenting Gram-negative bacilli - Khoo, Bo Yan (2023)
NG-Test CARBA 5 (NG-Biotech) is a rapid in vitro multiplex immunoassay for the phenotypic detection and differentiation of the "big five" carbapenemase families (KPC, OXA-48-like, VIM, IMP, and NDM). Version 2 of this assay was evaluated alongside the Xpert Carba-R assay (Cepheid, Inc.), the modified carbapenem inactivation method (mCIM), and the CIMTris assay, with a collection of carbapenem-resistant non-fermenting Gram-negative bacilli comprising 138 Pseudomonas aeruginosa and 97 Acinetobacter baumannii isolates. Whole-genome sequencing (WGS) was used as the reference standard. For P. aeruginosa, NG-Test CARBA 5 produced an overall percentage agreement (OPA) with WGS of 97.1%, compared with 92.8% forXpert Carba-R and 90.6% for mCIM. For A. baumannii, as OXA-type carbapenemases (non-OXA-48) are not included, both the NG-Test CARBA 5 and Xpert Carba-R only had an OPA of 6.2%, while the CIMTris performed well with an OPA of 99.0%. The majority of A. baumannii isolates (95.9%) tested falsely positive for IMP on NG-Test CARBA 5; no IMP genes were found on WGS. No clear cause was found for this phenomenon; a cross-reacting protein antigen unique to A. baumannii is a possible culprit. NG-Test CARBA 5 performed well for carbapenemase detection in P. aeruginosa. However, results from A. baumannii isolates should be interpreted with caution.